Transient Receptor Potential (TRP) Channels - Samanta, Amrita (Subcell Biochem, 2018)
Transient Receptor Potential (TRP) channels are evolutionarily conserved integral membrane proteins. The mammalian TRP superfamily of ion channels consists of 28 cation permeable channels that are grouped into six subfamilies based on sequence homology (Fig. 6.1). The canonical TRP (TRPC) subfamily is known for containing the founding member of mammalian TRP channels. The vanilloid TRP (TRPV) subfamily has been extensively studied due to the heat sensitivity of its founding member. The melastatin-related TRP (TRPM) subfamily includes some of the few known bi-functional ion channels, which contain functional enzymatic domains. The ankyrin TRP (TRPA) subfamily consists of a single chemo-nociceptor that has been proposed to be a target for analgesics. The mucolipin TRP (TRPML) subfamily channels are found primarily in intracellular compartments and were discovered based on their critical role in type IV mucolipidosis (ML-IV). The polycystic TRP (TRPP) subfamily is a diverse group of proteins implicated in autosomal dominant polycystic kidney disease (ADPKD). Overall, this superfamily of channels is involved in a vast array of physiological and pathophysiological processes making the study of these channels imperative to our understanding of subcellular biochemistry.